2017
DOI: 10.3892/mmr.2017.7401
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibition reduces growth and adhesion of hepatocellular carcinoma cells in vitro

Abstract: Mechanistic target of rapamycin (mTOR) signaling is typically increased in hepatocellular carcinoma (HCC). A panel of HCC cell lines (HepG2, Hep3B and HuH6) was exposed to various concentrations of the mTOR inhibitors, everolimus and temsirolimus, in order to investigate their effects on cell growth, clonal formation, cell cycle progression, and adhesion and chemotactic migration using MTT and clonal cell growth assays, fluorometric detection of cell cycle phases and a Boyden chamber assay. In addition, integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It is thought that the activation of mTOR is associated with the pathogenesis and aggressiveness of liver cancer. In vitro and animal studies have shown that mTOR inhibitors could be effective for the treatment of liver cancer (11,13,15,29). However, clinical trials have failed to demonstrate significant improvement in the prognosis in of patients with liver cancer (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that the activation of mTOR is associated with the pathogenesis and aggressiveness of liver cancer. In vitro and animal studies have shown that mTOR inhibitors could be effective for the treatment of liver cancer (11,13,15,29). However, clinical trials have failed to demonstrate significant improvement in the prognosis in of patients with liver cancer (17).…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is overexpressed in approximately 40% of liver cancer, and liver cancer with overexpression of mTOR follows an unfavorable clinical course (11). Preclinical studies showed that inhibition of the mTOR pathway suppress the development of liver cancer (12)(13)(14)(15)(16). However, clinical trials of mTOR inhibitors Inhibitor for protein disulfide-isomerase family A member 3 enhances the antiproliferative effect of inhibitor for mechanistic target of rapamycin in liver cancer: An in vitro study on combination treatment with everolimus and 16F16…”
Section: Introductionmentioning
confidence: 99%
“…Loss-of-function of tuberin (TSC2), a key negative regulator of mTORC1, is common in HCC (338). Finally, the majority of therapeutic interventions in HCC aim at decreasing AKT-mTORC1 signaling (339)(340)(341)(342).…”
Section: Liver Cirrhosis and Advanced Hccmentioning
confidence: 99%
“…EVR in combination with a reduced dose of TAC results in better renal function than that seen with standard immunosuppression (IS) with TAC alone . Furthermore, EVR had been shown to exert antiproliferative effects and antitumor activity on hepatoma cells in vitro . However, in either clinical or in vivo trials, clear evidence is still missing confirming that the application of EVR could reduce recurrence rates of hepatocellular carcinoma (HCC) after LT .…”
mentioning
confidence: 99%
“…(1)(2)(3) Furthermore, EVR had been shown to exert antiproliferative effects and antitumor activity on hepatoma cells in vitro. (4,5) However, in either clinical or in vivo trials, clear evidence is still missing confirming that the application of EVR could reduce recurrence rates of hepatocellular carcinoma (HCC) after LT. (6)(7)(8) New evidence suggests that EVR protects LT patients from the development of donor-specific antibodies, which may complicate longterm graft viability. (9,10) Moreover, the administration of EVR is related to a reduction in the risk of cytomegalovirus infections among immunosuppressed patients (11)(12)(13) and has been shown to reduce the viral load of LT patients infected with hepatitis C virus genotypes 2a and 3.…”
mentioning
confidence: 99%